FOSTERING SOFT SKILLS AND CREATIVITY IN HIGHER EDUCATION: THE ROLE OF ACTIVE LEARNING AND EMPATHETIC TEACHING - Wojciechowska, M.; Gomes, S. (17th International Conference on Education and New Learning Technologies, 2025)
Higher education often emphasizes content delivery over the development of soft skills, leaving students unprepared for interpersonal and creative challenges in the modern world. This paper explores how active learning methodologies and creative pedagogies can transform teaching by fostering empathy, adaptability, and innovation. Using a qualitative approach, active learning techniques such as group reflections, discussions, hands-on projects addressing complex problems, and role-playing scenarios were integrated into courses like "Introduction to Design Thinking" and "Public Presentations with Theater Techniques." These methodologies aimed to enhance self-awareness, creativity, and confidence among students. Data collection included implementing these techniques, reflective practice documented in a "reflective field diary," and anonymous student surveys conducted through the university platform. The surveys focused on pedagogical methods, skill development, learning outcomes, and the impact of classes on students’ academic and personal lives. Preliminary findings reveal that integrating active pedagogies improves complex problem-solving skills, evidenced by innovative solutions and prototypes in design thinking projects. Moreover, student-centered approaches fostered soft skills like teamwork, effective communication, and creativity, creating a more inclusive learning environment, as reflected in survey responses. Insights from reflective diaries highlighted the role of vulnerability as a catalyst for building confidence and engagement, supporting safe spaces for individual and group reflection in the classroom. This study underscores the transformative potential of active learning and creative pedagogies in higher education. By promoting empathy, adaptability, creativity, and innovation, these strategies go beyond traditional academic outcomes, supporting the holistic development of students as engaged, reflective, and socially aware individuals. The integration of empathetic teaching practices and student-centered methodologies contributes not only to a more inclusive and dynamic classroom environment but also to the cultivation of essential 21st-century competencies. As higher education institutions face increasing demands to prepare students for complex, interdisciplinary, and human-centered challenges, this research offers valuable insights into how pedagogical innovation can bridge the gap between knowledge acquisition and personal growth. Ultimately, it highlights a compelling case for reimagining educational practices to empower learners who are not only skilled professionals but also compassionate and creative contributors to society.